Observation of reverse saturable absorption of an X-ray laser - Cho, BI; Cho, MS; Kim, M; Chung, H-K; Barbrel, B; Engelhorn, K; Burian, T; Chalupský, S; Ciricosta, O; Davovski, GL; Hájková, V; Holmes, M; et al. (American Physical Society, 2017)
A nonlinear absorber in which the excited state absorption is larger than the ground state can undergo a process called reverse saturable absorption (RSA). It is a well-known phenomenon in laser physics in the optical regime, but is more difficult to generate in the x-ray regime, where fast non-radiative core electron transitions typically dominate the population kinetics during light matter interactions. Here, we report the first observation of decreasing x-ray transmission in a solid target pumped by intense x-ray free electron laser pulses. The measurement has been made below the K-absorption edge of aluminum, and the x-ray intensity ranges are 10^16~17 W/cm2. It has been confirmed by collisional radiative population kinetic calculations, underscoring the fast spectral modulation of the x-ray pulses and charge states relevant to the absorption and transmission of x-ray photons. The processes shown through detailed simulations are consistent with reverse saturable absorption, which would be the first observation of this phenomena in the x-ray regime. These light matter interactions provide a unique opportunity to investigate optical transport properties in extreme state of matters, as well as affording the potential to regulate ultrafast XFEL pulses.